KAUSHAL ELECTRONICS - Prashant (International Journal of Research -GRANTHAALAYAH, 2019)
The theory of special connectivity [1] has proposed a new theory for gravity in terms of Kaushal constant [2]. The paper shows the effect of this constant on the branch of electronics. Fundamental frequency of vibration has been calculated. Also, Values of charge, current, voltage, capacitance and inductance have been derived.